The importance of nonobstructive plaque characteristics in symptomatic and asymptomatic coronary artery disease - de Knegt, Martina C.; Linde, Jesper J.; Sigvardsen, Per E.; Engstrøm, Thomas; Fuchs, Andreas; Jensen, Andreas K.; Elming, Hanne; Kühl, J. Tobias; Hansen, Peter R.; Høfsten, Dan E.; Kelbæk, Henning; Nordestgaard, Børge G.; et al. (Journal of cardiovascular computed tomography, 2024)
We examined obstructive and nonobstructive plaque volumes in populations with subclinical and clinically manifested coronary artery disease (CAD) using quantitative computed tomography (QCT). 855 participants with CAD (274 asymptomatic individuals, 254 acute chest pain patients without acute coronary syndrome (ACS), and 327 patients with ACS) underwent QCT of proximal coronary segments to assess participant-level plaque volumes of dense calcium, fibrous, fibrofatty, and necrotic core tissue. Nonobstructive (<50% stenosis) plaque volumes were greater than obstructive plaque volumes, irrespective of population (all p<0.0001): Asymptomatic individuals (mean (95% CI)): 218 [190-250] vs. 16 [12-22] mm3; acute chest pain patients without ACS: 300 [263-341] vs. 51 [41-62] mm3; patients with ACS: 370 [332-412] vs. 159 [139-182] mm3. After multivariable adjustment, nonobstructive fibrous and fibrofatty tissue volumes were greater in acute chest pain patients without ACS compared to asymptomatic individuals (fibrous tissue: 122 [107-139] vs. 175 [155-197] mm3, p<0.01; fibrofatty tissue: 44 [38-50] vs. 71 [63-80] mm3, p<0.01. Necrotic core tissue was greater in ACS patients (29 [26-33] mm3) compared to both asymptomatic individuals (15 [13-18] mm3, p<0.0001) and acute chest pain patients without ACS (21 [18-24] mm3, p<0.05). Nonobstructive dense calcium volumes did not differ between the three populations: 29 [24-36], 29 [23-35], and 41 [34-48] mm3, p>0.3 respectively. Nonobstructive CAD was the predominant contributor to total atherosclerotic plaque volume in both subclinical and clinically manifested CAD. Nonobstructive fibrous, fibrofatty and necrotic core tissue volumes increased with worsening clinical presentation, while nonobstructive dense calcium tissue volumes did not.